Penerapan Algoritma Golomb Coding Pada Aplikasi Kompresi Short Message Service (SMS) - Linni Hairani Butar Butar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The use of this android-based mobile phone is very easy to convey a message to the intended person. Like being able to send messages via WA, Telegram, Instagram and other applications. So in this way humans are faster in sending a message. Although it is not widely used, there are still people who send messages via SMS, and not everyone also has a mobile phone with an Android operating system. The problem in using this sms is that the more text that is sent, it will cost a lot, if it exceeds 160 characters, the content of the message will be sent into two sms. This problem can be solved by abbreviating the message sent, but another problem arises, namely a misunderstanding in reading the contents of the message because many do not understand the abbreviated message